Vận dụng mô hình giáo dục STEM trong phát triển kĩ năng viết sáng tạo cho học sinh trung học phổ thông theo phương pháp dạy học dự án - Nguyễn, Thu Hường; Nguyễn, Thị Hồng Ánh; Nguyễn, Như Ánh (Tạp chí Giáo dục, 2025)
STEM education is an educational method that aims to equip students with scientific knowledge associated with their practical applications. The This article focuses on proposing five principles for application and a 5-step process for applying STEM education in developing creative writing skills for high school students using the project-based teaching method to contribute to the implementation of the goals of the 2018 General Education Program; at the same time, it provides and supports teachers to design STEM lessons to implement in the teaching process of subjects in the general education program according to the integrated approach within the subject or interdisciplinary integration and comprehensive development of students' competence.